Characterization of high electron mobility transistor fabricated on hydride vapor phase epitaxy‐grown GaN templates containing various Fe concentrations. Issue 8 (20th March 2017) - Sugimoto, K.; Nishihira, T.; Arita, N.; Dempo, Y.; Okada, N.; Tadatomo, K.
Abstract : An AlGaN/GaN high electron mobility transistor (HEMT) structure was grown on a semi‐insulating (SI) GaN layer or substrate to suppress a leakage current and achieve a high breakdown voltage. Fe can be used as doping material to obtain SI‐GaN. However, the relationship between the Fe concentration in the GaN layers and its influence on HEMT characteristics has not yet been investigated. In this study, we therefore investigated the influence of Fe concentration in the GaN layers on HEMT characteristics. The GaN layers containing several Fe concentrations were grown by hydride vapor phase epitaxy (HVPE). The Fe concentration was varied from 3 × 10 17 to 3 × 10 20 atoms cm −3 . It was determined that the source‐drain current ( I DS ) decreased as the Fe concentration increased. In the case of a low Fe concentration of 3 × 10 17 atoms cm −3, I DS was almost the same as that of HEMT on the non‐Fe‐doped GaN template. Thus, HEMT characteristics deteriorated as the Fe concentration increased. The channel layer played a role in blocking the adverse effects of Fe doping on the two‐dimensional electron gas concentration in AlGaN/GaN. Moreover, it was shown that the GaN channel layer must become thicker as the Fe concentration of the GaN layers increases.